Bulgaria : Public Expenditures for Growth and Competitiveness - World Bank (Washington, DC, 2013)
Bulgaria's economy performed relatively well during the crisis and the economy is reviving. In comparison with other Tenth European Union (EU10) countries, for Bulgaria the drop in Gross Domestic Product, or GDP growth was below the median, fiscal performance deteriorated less, and public debt stayed among the lowest in the entire EU. In late January 2011 the EC concluded that in 2010 Bulgaria had made significant progress in deficit reduction and is on track to exit the excessive deficit procedure in 2011. The large macroeconomic imbalances observed in 2005-08 had been corrected by 2010 with relatively little negative impact on growth relative to other EU10 countries. Since late 2010 Bulgaria's recovery has been driven by net exports; investment and consumption are recovering more slowly. As long as the economic environment remains favorable and structural reforms are implemented as planned, the economy should reach and even exceed its pre-crisis level in 2012. This report is intended to inform policy makers, the international community, and civil society about Bulgaria's recent economic performance and its options for reforming public spending to enhance competitiveness and growth. It first reviews Bulgaria's growth strategy and its fiscal adjustment over the last several years and the medium-term challenges it confronts. The report then analyzes Bulgaria's export performance to identify comparative advantages and outline policy options to enhance competitiveness in the medium term. Reforms should focus on improving the productivity of the public sector to enhance service delivery, improve the business environment, and upgrade infrastructure. The report identifies two general areas for reform: (i) the wage bill and public employment; and (ii) management of public investment.